The Effect of Engineering Design-based STEM Activities on the Refugee Students’ Sense of School Belonging - Sema Altun Yalçın; Şeyma Güvenç Günsel; Zehra Çakır (Universitas Pendidikan Indonesia, 2022)
In the research, the effect of engineering design-based STEM activities on the school belonging to seventh-grade refugee students was examined. A mixed-method was used in the research. The research sample consists of 32 Syrian refugee students studying in the 7th grade in the fall semester of the 2019-2020 academic year. The study lasted for ten weeks, with two lessons per week. In addition, the “School Attachment Scale for Children and Adolescents” was used as a quantitative data collection tool. On the other hand, qualitative data collection tools were used as “STEM Education Reflective Diary Form, STEM Education Interview Form, and Teacher Interview Form,” which were prepared based on quantitative scale items. Statistical methods were used to analyze the quantitative data obtained in the research, and content analysis was used in the qualitative data analysis. The quantitative data showed a significant difference between the pre-test and post-test scores. As a result, It was concluded that the engineering design-based STEM activities carried out contributed positively to the individual and social development of Syrian refugee students; their positive attitudes towards the lesson and the teacher impacted their sense of belonging to the school.